2021
DOI: 10.1007/s10071-021-01471-x
|View full text |Cite
|
Sign up to set email alerts
|

Bodily emotional expressions are a primary source of information for dogs, but not for humans

Abstract: Dogs have remarkable abilities to synergise their behaviour with that of people, but how dogs read facial and bodily emotional cues in comparison to humans remains unclear. Both species share the same ecological niche, are highly social and expressive, making them an ideal comparative model for intra- and inter-species emotion perception. We compared eye-tracking data from unrestrained humans and dogs when viewing dynamic and naturalistic emotional expressions in humans and dogs. Dogs attended more to the body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 75 publications
8
42
0
Order By: Relevance
“…Thus, human and dog stimuli appear to be equally salient for dogs. This is in line with previous behavioural studies suggesting, for example, no significant difference in the perception of human or dog emotional facial [34], whole-body cues [77], or images of social interactions [67].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, human and dog stimuli appear to be equally salient for dogs. This is in line with previous behavioural studies suggesting, for example, no significant difference in the perception of human or dog emotional facial [34], whole-body cues [77], or images of social interactions [67].…”
Section: Discussionsupporting
confidence: 93%
“…The absence of a further sub-specialization for face vs. body perception in the occipito-temporal cortex of dogs might indeed indicate that dogs in comparison to humans focus more on whole body social cues rather than on specific sub-parts. This interpretation is notably well in line with a recent comparative eye-tracking study [78].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We showed that visual configurations used by cats when interacting with other cats or with humans differed greatly: in cat–cat interactions, the position of the ears appeared to be the most significant feature and when approaching humans, usually only one visual configuration is used, featuring the tail up. Correia-Caeiro et al [ 44 ], dealing with dog–humans interactions, made the important point that what is important for one species might not be so for another one, especially when very phylogenetically distant.…”
Section: Discussionmentioning
confidence: 99%
“…In interspecific interactions, each species has to adapt and adjust to the communicative repertoire of the other species. Humans in particular may learn through associative learning the meaning of the signals given by their pets [ 44 ] Ear or tail positions are easily perceived by humans and interpreted. Artificial selection in cats has been less active than that in dogs [ 49 ].…”
Section: Discussionmentioning
confidence: 99%